Pendugaan Masa Kadaluarsa Ubi Kayu (Manihot esculenta Crantz) Instan pada Beberapa Bahan Kemasan - Pande Elza Fitriani (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2015)
The shelf life estimating of instant cassava were determined by analyzing the moisture sorption of it. The instant cassava was made into cube form with dimension of 0,5 cm x 0,5 cm x 0,5 cm and used as samples to analyzing the moisture sorption isotherm characteristic. Moisture sorption isotherms of it were determined at 28±2°C using standard gravimetric static method over a range of equilibrium relative humidity (ERH) from 6.90%-97.90%. The experimental data were fitted by Henderson model and well predicted almost at each point of aw. The data of instant cassava’s moisture sorption isotherm followed type II behavior. The shelf life of it were calculated using Labuza equation with three different packaging materials: low density polyethylene (LDPE) of 0.03 mm thickness, polypropylene (PP) of 0.03 mm thickness and retort pouch. The shelf life of instant cassava using those three packaging materials were obtained for 103, 88 and 3502 days, respectively.